(untitled) (Al-Mansour Journal, 2022)
Use of waste rubber in concrete mix and RC structures has attracted great attention in recent decades. However, attention has been paid to reuse the tire strips in RC parts. In the current study, a finite element (FE) modeling has been proposed for the non-linear analysis of six RC joints with tire strips aggregate. The model includes of the effects of difference ratios of the tire strips replacing aggregate and the size of the strips. As for the credibility of the method, some available experimental works were modeled and non-linearly analyzed using ANSYS 10. The results showed that the model can predict the experimental works with good accuracy. At the end and as a case study, the reference joint specimen was the best accuracy with the FE analysis the other specimens results were accrued with the experimental results less than the reference specimen, the difference between the FE analysis and the experimental analysis increased as the ratio of the tire strips increased with different size of strips.